Caves as geoheritage resource in remote desert areas: a preliminary evaluation of Djara Cave in the Western Desert of Egypt - Abdel Maksoud, Kholoud M.; Baghdadi, Mahmoud I.; Ruban, Dmitry A. (Geologos, 2021)
Caves are rare in northeast Africa and, thus, deserve attention as potential geoheritage objects (geosites). Assessment of Djara Cave and its vicinity (Western Desert, Egypt) has permitted to document unique features, such as the cave itself as a peculiar subsurface landform, speleothems providing data for palaeoenvironmental reconstructions, rock art demonstrating elements of past landscapes, siliceous nodules weathered from Eocene limestones and a network of dry drainage channels indicative of wetter palaeoenvironments. These features are assigned to geomorphological, sedimentological and palaeogeographical types of geoheritage. Djara Cave and its vicinity are proposed as a geosite of national rank; it is vulnerable to anthropogenic stress and needs geoconservation measures and instalment of interpretative signs. This geosite is already popular among tourists, and can be used for further tourism development. More generally, the presence of caves in Egyptian desert areas makes possible the recognition of national speleological heritage that requires special country-level strategies of management.